Multiple Sclerosis Diagnosis and Treatment II - Rivera, Víctor M. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book "Multiple Sclerosis: Diagnosis and Treatment" provides a collection of selected articles published in Biomedicines as part of Volume II addressing current issues on this major inflammatory demyelinating neurological disorder. The articles describe recent advances and discoveries in the molecular and cell microenvironment contributing to neuro-inflammation in the brain and spinal cord. The role of the neurofilaments light chain as a serological biomarker of axonal and neuronal degeneration of the CNS is presented not just as a sensitive diagnostic tool, but also as an indicator of treatment responses. The new generation of therapeutic molecules belonging to the sphingosine-1-phosphate class are discussed, and their potential as disease-modifying treatment is considered. Investigations into the intimate molecular mechanisms of highly active MS, disclosed clinically and by MRI, are discussed by researchers proposing that the expression of RNAs in peripheral blood cells is a biomarker of highly active disease. The book also addresses important clinical and epidemiological aspects of pediatric MS and that in multi-ethnic cohorts.